Litter fall production and nutrient adition by young plantations of Eucalyptus in the southern plateau of Santa Catarina, Brazil - Urbano, Cíntia Neves; Simonete, Marcia Aparecida; Ernani, Paulo Roberto; Chaves, Djalma Miler; Moro, Letícia (Revista Ecologia e Nutrição Florestal - ENFLO, 2018)
Litter deposition and decomposition of litter may vary with age and, during the year, with climatic seasons. The objective of this study was to quantify the litter produced and the transfer of nutrients to the soil throughout the year in young stands of Eucalyptus dunnii Maiden. Field experiments were carried out over an Haplumbrept, in Bocaina do Sul, Santa Catarina State, Southern Brazil, with one, two and three year-old stands Three plots were installed int each plantation age, in order to collect plant litter. Litter sampling was performed monthly, during the entire year of 2011. It was used 11 collectors of 0.25 m² in each plot. It was quantified the deposition of dry matter of each component of litter (leaves, branches and bark) over the seasons, and determined the levels of P, S, K, Ca and. The three stands showed similar annual litter depositions, and about 95% of the total was constituted by leaves. Litter deposition presented seasonality, with the lowest deposition in the winter and the highest in the summer. Litter deposition was seasonal, with lower deposits in winter and higher in summer 99% P, 97% K, 97% Ca, 96% Mg and 98% S. The magnitude of values was: Ca > K > Mg > S > P.